Efektivitas dan Kontribusi Pajak Bumi dan Bangunan Pedesaan dan Perkotaan terhadap Pendapatan Asli Daerah Kabupaten Bojonegoro Tahun 2018-2022 - Noviani, Siti Alya; Andhaniwati, Erry (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The purpose of this study is to determine the level of effectiveness of land and building tax revenue and how much the contribution of land and building tax to Bojonegoro District Original Revenue. Data collection techniques are carried out using documentation techniques. The data analysis technique used is the effectiveness ratio analysis technique and the contribution ratio analysis technique. This research is a quantitative descriptive research, which is based on an explanation of the numbers. The data in this study are in the form of targets and realization of Rural and Urban Land and Building Tax revenues, as well as targets and realization of Local Own Revenue for Bojonegoro Regency overnight 5 (five) years. The results of the study show that the effectiveness of the Bojonegoro Regency land and building tax from 2018 to 2022 is in the very effective category. Meanwhile, its contribution is included in the category of very less contribution to Regional Original Revenue. It is hoped that the Bojonegoro Regency Government will continue to explore potentials that can increase land and building tax revenues as well as increase the contribution of land and building tax. They need to optimize land and building tax revenues, such as adding tax collection facilities. Keywords: Effectiveness; Contributions; Land and Building Tax